Intelligent Systems Design and Applications Information and Network Security, Volume 3 - Abraham, Ajith; Pllana, Sabri; Hanne, Thomas; Siarry, Patrick (Lecture Notes in Networks and Systems, 2024)
XVII, 479 p. 155 illus., 124 illus. in color.